MENINGKATKAN MINAT BELAJAR SISWA PADA PENDIDIKAN AGAMA KRISTEN MENGGUNAKAN MEDIA PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 - Markuat; Reni Triposa; Yonatan Alex Arifianto (Metanoia, 2022)
Increasing interest in learning is the most important element in shaping the attitudes, character and enthusiasm of students to sharpen knowledge and intellect in line with technological advances. This study uses a qualitative approach with descriptive methods and analyzes the data using a literature study, which can provide information on objectives and clear understanding in increasing interest in learning Christian religious education during the Covid-19 pandemic. In this study also provides useful results for researchers as well as for educators and students to find out how important it is to increase interest in the learning process. This learning provides encouragement for students to be even more active in seeking to explore knowledge and experience independently at home because during this pandemic the government has stipulated a rule that schools cannot carry out face-to-face learning with students and students are encouraged to learn from home with assistance. guidance from each parent so that the process of student teaching and learning activities is improved and runs well.